ELIMAIA-ELIMED: a new user platform for radiobiological research utilizing laser-driven protons - Bláha, P.; Prise, K. M.; Borghesi, M.; Cammarata, F. P.; Catalano, R.; Chaudhary, P.; Cirrone, G. A. P.; Davídková, M.; Doria, D.; Forte, G. I.; Grepl, F.; Hideghéty, K.; et al. (Frontiers in Physics, 2025)
The ELIMAIA-ELIMED beamline, powered by the L3 HAPLS petawatt laser, enables the irradiation of biological samples with intermediate-energy laser-driven protons (LDP) in a multi-shot regime. In the pilot radiobiological experiment, protons with a mean energy of ∼24 MeV and doses up to ∼14 mGy per shot, with ∼4 ns bunch duration, were used to irradiate AG01522 normal human skin fibroblasts. The shortest irradiation time achieved was down to ∼17 min/Gy, while the mean and peak dose rates reached ∼1 × 10−3 and 3.5 × 106 Gy/s, respectively. The cells were exposed to doses ranging from ∼0.4 to 1.5 Gy and analyzed for DNA damage, with double-strand breaks visualized as 53BP1 foci. Despite the differences in shot exposures between the multi-shot LDP and the previous experiments (at other facility) with single-shot LDP, similar DNA damage responses were observed. Results with conventionally accelerated protons align closely with the corresponding single-shot LDP samples. These experimental results were achieved as part of the flagship experiment FLAIM (within the IMPULSE EU-funded project) and serve as an initial demonstration of the ELIMAIA-ELIMED platform’s potential for advanced radiobiological research, creating new opportunities for such studies utilizing laser-driven ion sources.